Case report: A study on the pathology of mandibular osteosarcoma with hepatic metastasis in a giant panda - Xiong, Zongliang; Ling, Shanshan; Li, Caiwu; Deng, Linhua; Wei, Tingting; He, Ming; Wang, Chengdong; Luo, Qihui; Li, Desheng; Cheng, Zhengli (Frontiers in Veterinary Science, 2025)
During routine health examinations, an abnormal growth was detected in the oral cavity of a male giant panda. A malignant tumor, osteosarcoma, was diagnosed through CT (computed tomography) scans and pathological examination of biopsy samples. After two attempts at “tumor reduction surgery” with no improvement, the condition stabilized following particle implantation and arterial infusion interventional therapy. The following year, a CT scan revealed a highly similar mass in the left lumbar muscle, which showed no improvement despite chemotherapy, leading to death 1 month later. Post-mortem examination and tissue pathological diagnosis confirmed osteosarcoma characteristics in the facial, lumbar, and liver masses. The giant panda was diagnosed with osteosarcoma with liver metastasis based on integrated pathological and gross anatomical observations. This case represents the first report of osteosarcoma with liver metastasis in a giant panda, providing valuable data and references for future clinical diagnosis and treatment of tumors in giant pandas.